PENGARUH PENERAPAN MODEL INKUIRI TERHADAP HASIL BELAJAR IPA SISWA DI SEKOLAH DASAR - Islam, Umi Rawdhatul; Rosnita, Rosnita; Asran, Mastar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to analyze the effect of implemantation inquiry model on nature science learning outcomes of students in 5th grade of 36 Pontianak Kota public elementary school. The Method which used in this research is experiment with a quasi experimental form and nonequivalent control group design. The Population in this research are all students in fifth grade of 36 Pontianak Kota public elementary school that totaling 49 students. The sampling technique in research using nonprobability sampling with purposive sampling type. Data collection technique which used are direct observation and measurement techniques. The research instrument used was a written test with multiple choice form. The result of the data analyze, obtained an average post-test in experimental class obtained at 64,886 while the control class is 56,190. The result of t test obtained tcount (2,132) > ttabel (2,020), its mean Ha accepted and H0 is rejecte. The effect size result is 0,470 with medium criteria. The conclusion in this study is there is the effect of implementation inquiry model on natural science learning outcomes of 5th grade students of 36 Pontianak Kota public elementary school with medium criteria.. Keywords : The Effect, Inquiry Model, Learning Outcomes, Natural Science